An Observation on the Interrelationship Between the Gravitational Weight and the Area of a Flat Sheet: A New Concept of Rapid Measurement of Areas Bended by Irregular Outlines - Syama P. Bhattacharya; Asis Ghosh (International Journal of Mathematics And its Applications, 2018)
An accurate measurement of a bended flat area with many bends and deflections is practically impossible to perform using any of the existing methods of mensuration. Therefore, an alternative method has been investigated which insists on the measurement of gravitational weight of the portion of paper occupied by the area of a map. However, the map should be drawn on a thin flat sheet having the quality of uniform gravitational weight. A simple method for the selection of an uniform thin sheet has also been discussed. A theorem, I = W10^2 has been proposed for the rapid determination of index of any flat surface irrespective of sizes and geometric forms.